2019
DOI: 10.1097/prs.0000000000006278
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Analysis of Sensory and Motor Axons in Branches of the Human Brachial Plexus

Abstract: Background: The topographic distribution through histologic analysis of motor and sensory axons within peripheral nerves at the brachial plexus level is not clearly defined, as there has previously been little need to appreciate this microanatomy. A desire to better understand the topography of fascicle groups developed with the introduction of targeted muscle reinnervation. Methods: Fourteen bilateral brachial plexus specimens from seven fresh human ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…Immunohistochemistry is a powerful tool in analyzing human neuronal tissue at the molecular level. Typically, neuronal tissue is harvested from organ donors (Tschopp et al 1984 ; Eftekhari and Edvinsson 2011 ; Gesslbauer et al 2017 ; Mioton et al 2019 ; Stakenborg et al 2020 ; Dominguez-Alvaro et al 2021 ; Shiers et al 2021 ) or body donors (Rein et al 2013 , 2015 , 2020 ; Pascual-Font et al 2016 ; Lienbacher et al 2019 ). Harvesting neuronal tissue from organ donors requires a high administrative workload and is often prohibited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry is a powerful tool in analyzing human neuronal tissue at the molecular level. Typically, neuronal tissue is harvested from organ donors (Tschopp et al 1984 ; Eftekhari and Edvinsson 2011 ; Gesslbauer et al 2017 ; Mioton et al 2019 ; Stakenborg et al 2020 ; Dominguez-Alvaro et al 2021 ; Shiers et al 2021 ) or body donors (Rein et al 2013 , 2015 , 2020 ; Pascual-Font et al 2016 ; Lienbacher et al 2019 ). Harvesting neuronal tissue from organ donors requires a high administrative workload and is often prohibited.…”
Section: Discussionmentioning
confidence: 99%
“…Today there is increasing interest in analyzing human neuronal tissue including the brain (Waldvogel et al 2006 ; Blair et al 2016 ), spinal cord (Tschopp et al 1984 ; Eftekhari and Edvinsson 2011 ; Shiers et al 2021 ), and peripheral nerves (Gesslbauer et al 2017 ; Mioton et al 2019 ; Stakenborg et al 2020 ) by immunohistochemistry to better understand neuronal function. As there is a need for high tissue quality, fresh tissue from organ donors is often preferred, although tissue collection is very challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Speci cally, 99.5 out of 100 percent of the axons leaving the spinal cord via the anterior root exhibited ChAT immunoreactivity and the same value (more than 99 percent) of cholinergic axons was counted in fresh spinal cord obtained from heart-beating organ donors (Gesslbauer et al, 2017). This important information suggests that neuronal tissue from body donors is suitable for quantitative analyses of molecularly different axons in mixed peripheral nerves and may be an alternative to organ donors tissue (Gesslbauer et al, 2017;Mioton et al, 2019;Stakenborg et al, 2020). Altogether, present ndings underline that accurate interpretation of immunohistochemical data is possible in neuronal tissue harvested from body donors.…”
Section: Discussionmentioning
confidence: 78%
“…Normally, motor and sensory fibers in peripheral nerves maintain a high degree of somatotopy despite frequent anastomoses between perineurial sheaths. Thus, motor fibers for specific muscle groups and sensory fibers for specific cutaneous areas tend to remain grouped as fascicles or within fascicles along the length of peripheral nerves (Badia et al, 2010;Mioton et al, 2019). In the case of the Gli1 nulls, SBF-SEM revealed that the cellular sheaths forming MFs are not confined to a fixed set of axons but rather anastomose along their length (see Movie 1).…”
Section: Potential Effects Of Mfs On Peripheral Nerve Functionmentioning
confidence: 99%